Girard's mimetic theory across the disciplines - Cowdell, Scott; Fleming, Chris; Hodge, Joel (Violence, desire, and the sacred, 2012)
Showcases the application of Rene Girard's mimetic theory across a range of disciplines, including philosophy, religious studies, literature and cultural studies.